Observability of paramagnetic NMR signals at over 10 000 ppm chemical shifts: dedicated to Prof. Frank H. Köhler on the occasion of his 80th birthday - Ott, Jonas C.; Suturina, Elizaveta A.; Kuprov, Ilya; Nehrkorn, Joscha; Schnegg, Alexander; Enders, Markus; Gade, Lutz H. (Angewandte Chemie. International edition, 2021)
We report an experimental observation of 31P NMR resonances shifted by over 10 000 ppm (meaning percent range, and a new record for solutions), and similar 1H chemical shifts, in an intermediate-spin square planar ferrous complex [tBu(PNP)Fe-H], where PNP is a carbazole-based pincer ligand. Using a combination of electronic structure theory, nuclear magnetic resonance, magnetometry, and terahertz electron paramagnetic resonance, the influence of magnetic anisotropy and zero-field splitting on the paramagnetic shift and relaxation enhancement is investigated. Detailed spin dynamics simulations indicate that, even with relatively slow electron spin relaxation (T1 ≈10−11 s), it remains possible to observe NMR signals of directly metal-bonded atoms because pronounced rhombicity in the electron zero-field splitting reduces nuclear paramagnetic relaxation enhancement.